Association between per- and polyfluoroalkyl substances and risk of hypertension: a systematic review and meta-analysis - Xiao, Fang; An, Ziwen; Lv, Junli; Sun, Xiaoyi; Sun, Heming; Liu, Yi; Liu, Xuehui; Guo, Huicai (Frontiers in Public Health, 2023)
Background: Existing evidence indicated that per- and polyfluoroalkyl substances (PFASs) exposure might increase the risk of hypertension, but the findings were discordant. So, we aimed to explore the relationship between PFASs and hypertension by this systematic review and meta-analysis. Methods: We searched PubMed, Embase, and the Web of Science for research published in English that examined the relationship between PFASs and hypertension before August 13, 2022. The random effect model was used to aggregate the evaluation by Stata 15.0 for windows. We also conducted subgroup analyses by region and hypertension definition. Besides, a sensitivity analysis was carried to detect the robustness of the finding. Results:The meta-analysis comprised 15 studies in total with 69,949 individuals. The risk of hypertension was substantially and positively correlated with exposure to perfluorooctane sulfonate (PFOS), (OR=1.31, 95% CI: 1.14-1.51), perfluorooctanoic acid (PFOA) (OR=1.16, 95% CI: 1.07-1.26), and perfluorohexane sulfonate (PFHxS) (OR=1.04, 95% CI: 1.00-1.09). However, perfluorononanoic acid (PFNA) exposure and hypertension were not significantly associated (OR=1.08, 95% CI: 0.99-1.17). Conclusion: We evaluated the link between PFASs exposure and hypertension and discovered that greater levels of PFOS, PFOA, and PFHxS are correlated with an increased risk of hypertension. However, further high-quality population research and pathophysiology investigations are required to shed light on the possible mechanism and demonstrate causation because of the considerable variability.